2017
DOI: 10.3201/eid2308.170162
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 and blaKPC-3 in Escherichia coli Sequence Type 744 after Meropenem and Colistin Therapy, Portugal

Abstract: Escherichia coli Ec36 was recovered from a patient in Portugal after treatment with meropenem and colistin. Besides an IncF plasmid with Tn1441d-blaKPC-3, already reported in clinical strains in this country, E. coli Ec36 co-harbored an IncX4::mcr-1 gene. Results highlight emerging co-resistance to carbapenems and polymyxins after therapy with drugs from both classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The P3 site appears to have particular characteristics in terms of the resistome. In addition to the genes already mentioned above (i.e., bla IMP , bla VIM and bla CTX−M ), other clinically relevant genes have also been detected at this site, such as mcr-5 genes, which confer resistance to colistin and which have recently been detected in plasmids from environmental, human and animal derived isolates (Sun et al, 2017;Tacão et al, 2017;Chen et al, 2018). Furthermore, in this site, the diversity of resistance genes found was superior to that of the other two sites (Supplementary Table S4).…”
Section: Analysis Of the Resistomementioning
confidence: 89%
“…The P3 site appears to have particular characteristics in terms of the resistome. In addition to the genes already mentioned above (i.e., bla IMP , bla VIM and bla CTX−M ), other clinically relevant genes have also been detected at this site, such as mcr-5 genes, which confer resistance to colistin and which have recently been detected in plasmids from environmental, human and animal derived isolates (Sun et al, 2017;Tacão et al, 2017;Chen et al, 2018). Furthermore, in this site, the diversity of resistance genes found was superior to that of the other two sites (Supplementary Table S4).…”
Section: Analysis Of the Resistomementioning
confidence: 89%
“…The bla KPC-2 and bla NDM was responsible for phenotypic resistance in 58% and 32% of the CRE strains in China, respectively [2]. Co-existence of mcr genes and different carbapenem resistance genes such as bla KPC-3 , bla NDM-5 , and bla NDM-16 have been sporadically reported in Enterobacteriaceae isolated from patients from different continents, among which E. coli was the most reported hosts [44][45][46]. Consistently, all mcr-1-positive CRE strains in this study belonged to E. coli, indicating E. coli was the major reservoir of such resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…In all mcr-1 –positive isolates, the gene was located in an IncX4-type plasmid ( Figure 2 ). Comparative genomics revealed that this plasmid (pAN_M1A) is circulating among diverse hosts (humans, pig, poultry) and the environment in many different countries, including Portugal ( 11 ). We identified bla KPC-3 in a Tn 4401d isoform in an ≈58-kb IncN-ST15 plasmid, a minority platform in our previous survey ( 5 ); bla CTX-M-15 was associated with multireplicon plasmid IncFII K -FIA-FIB.…”
Section: The Studymentioning
confidence: 99%